Engineering hybrid conductive electrochemically active biofilms enable efficient interfacial electron transfer and syntrophic carbon metabolism - Cai, Teng (2024)
Supply of carbon-based nanomaterials (e.g., carbon nanotubes, CNTs) to develop highly conductive electrochemically active biofilms (EABs) is a potential strategy for facilitating extracellular electron transfer (EET) in bioelectrochemical systems (BESs). Understanding of the underlying CNTs-mediated EET behaviors is helpful to further advance the practical application of BESs. Here, the cognitive influence of CNTs on bioelectrocatalytic activity and electron transfer efficiency of EABs were elucidated. CNTs can be embedded into EABs to form hybrid conductive biofilms (CNTs/EABs), achieving a high current density (7.4 ± 1.40 A m−2) and excellent coulombic recovery (46.0 ± 2.70 %) over 100 days of steady operation. The supply of CNTs can mitigate the dependence of exoelectrogens (such as Geobacter) on outer membrane cytochromes (OMCs) and conductive pili due to their down-regulated genes expression in CNTs/EABs, but it can significantly improve microbial carbon metabolism because physically high-conductive CNTs can establish rapid EET pathways, which may reduce the necessity for cells to invest metabolic energy in producing conductive pili and cytochromes that are required in the absence of CNTs. Such enhancement in electron transfer rate may be caused by the interfacial interaction between OMCs and CNTs, resulting in an order of magnitude higher than in the control (5.5 ± 1.60 s−1 vs. 0.28 ± 0.04 s−1) and without compromising of mass diffusion. This study provides comprehensive insight into the role of carbon-based nanomaterials in provoking interfacial electron transfer and renewable energy recovery.